Psychological features of professional self-determination of graduate students with autism spectrum disorder - Dzhafar-Zade, D.A.; Kalkova, G.V. (Bulletin of Practical Psychology of Education, 2025)
Context and relevance. Professional self-determination of persons with disabilities plays a special role in their socialization and self-realization in public life. The theoretical basis of the research is the theory of the essence of professional self-determination, which is based on the analysis of psychological personality traits, personal capabilities and abilities, a combination of motives with willingness to professional self-determination. Objective. To identify the influence of psychological characteristics of motivation on the readiness for professional self-determination among students with autism spectrum disorder. Hypothesis. Readiness for professional self-determination is positively correlated with motivation in students from among graduates with autism spectrum disorders. Methods and materials. The study involved college students - a group of subjects with autism spectrum disorders and a group of normotypic subjects, i.e. those corresponding to the statistical mental norm and not having mental disorders or developmental pathologies. In assessing readiness for professional self-determination, a map of readiness for professional self-determination was used, and the study of the psychological characteristics of motivation was carried out using methods for studying motivation for success, motivation for activity, and motivation for learning. Results. The results showed the presence of a relationship between motivation and readiness for professional self-determination, i.e. a moderate positive correlation was revealed, which means that the more pronounced the motivation, the higher the level of development of the general level of readiness for professional self-determination. Conclusions. Motivation is an important psychological feature among students with autism spectrum disorder, affecting their professional self-determination. The data obtained are of interest in the context of the work of psychologists and other specialists with people with autism spectrum disorder. As a result of the conducted research, we can recommend that psychologists in secondary vocational educational institutions work more specifically with the motivation of students with autism, as this has a positive effect on their readiness for professional self-determination. Контекст и актуальность. Профессиональное самоопределение лиц с ограниченными возможностями здоровья (ОВЗ) играет особую роль в их социализации и самореализации в общественной жизни. Теоретической основой исследования послужила теория сущности профессионального самоопределения, которая основывается на анализе психологических особенностей личности, личностных возможностей и способностей, совокупности мотивов с готовностью к профессиональному самоопределению. Цель. Выявить влияние психологических особенностей мотивации на готовность к профессиональному самоопределению у обучающихся из числа лиц с расстройствами аутистического спектра. Гипотеза. Готовность к профессиональному самоопределению положительно коррелирует с мотивацией у обучающихся из числа выпускников с расстройствами аутистического спектра. Методы и материалы. В исследовании приняли участие обучающиеся колледжей - группа обследуемых из числа лиц с расстройствами аутистического спектра и группа нормотипичных, т. е. соответствующих статистической психической норме, не имеющих психических расстройств и патологий развития. В оценке готовности к профессиональному самоопределению использовалась карта готовности к профессиональному самоопределению, исследование психологических особенностей мотивации проводилось с помощью методик изучения мотивации к успеху, мотивации к деятельности и мотивации обучения. Результаты. Результаты показали наличие взаимосвязи между мотивацией и готовностью к профессиональному самоопределению, выявлена умеренная положительная корреляция, что означает, что чем больше выражена мотивация, тем выше сформированность общего уровня готовности к профессиональному самоопределению. Выводы. Мотивация является важной психологической особенностью у обучающихся с расстройствами аутистического спектра, влияющей на их профессиональное самоопределение. Полученные данные представляют интерес в контексте работы психологов и других специалистов с лицами с расстройствами аутистического спектра. В результате проведенного исследования мы можем рекомендовать психологам в средних профессиональных образовательных организациях больше работать именно с мотивацией у обучающихся с аутизмом, т. к. это положительно влияет на их готовность к профессиональному самоопределению.